Ethics on the Edge: A Narrative Review of Communication Ethics in Journalism across Europe and Asia - Fitriyah, Aidatul; El-fattah, Hager Yehia Abd (Yayasan Sinergi Kawula Muda, 2024)
In the digital age, journalism faces a multitude of ethical challenges that demand critical reassessment of traditional media ethics. This narrative review investigates how communication ethics in journalism and social media have evolved, focusing on themes such as misinformation, transparency, media accountability, and cultural interpretations of ethical standards. Drawing on over fifty peer-reviewed studies sourced from Scopus, Google Scholar, and other databases, the review synthesizes empirical data and theoretical insights to evaluate the current state and future direction of media ethics. The methodology involved targeted keyword searches and thematic categorization of literature from 2010 to 2024, encompassing global perspectives with particular attention to Southeast Asia and Sub-Saharan Africa. The findings reveal that adherence to journalistic codes of ethics correlates strongly with public trust and media credibility. Furthermore, fact-checking initiatives, media literacy programs, and ethical journalism training have demonstrated effectiveness in countering misinformation and enhancing ethical engagement. Discussion highlights the systemic influence of political regimes, market forces, and cultural values in shaping journalistic practice. While regulatory and educational interventions show promise, structural barriers and digital disruption remain significant obstacles. The review concludes by recommending adaptive, context-sensitive ethical frameworks and greater international collaboration to strengthen journalistic integrity and combat misinformation in a rapidly changing media environment.